Ten sustainable steps infectious diseases professionals can take to mitigate the climate crisis - Shreya M. Doshi; Pamela Lee; Saul Hymes; Judith A. Guzman-Cottrill; Preeti Jaggi (Antimicrobial Stewardship & Healthcare Epidemiology)
Climate change and pollution harm the public. The healthcare industry disproportionately contributes to greenhouse gas emissions. Infection diseases professionals including infection preventionists and antimicrobial stewards are uniquely positioned to mitigate the environmental impact of our daily practices. We highlight 10 actionable steps that infectious disease professionals can incorporate into daily practices, thereby mitigating the impact of climate change.